Adding to the knowledge on Patient and Public Involvement: Reflections from an experience of co‐research with carers of people with dementia - Claudio Di Lorito; Maureen Godfrey; Marianne Dunlop; Alessandro Bosco; Kristian Pollock; Veronika van derWardt; Rowan H. Harwood (Wiley, 2020)
Abstract Background Patient and Public Involvement (PPI) in research ensures that publicly funded research reflects the priorities of the people who will be affected by its results. Co‐research, a branch of PPI, is equal partnership between academic researchers and members of the public, who steer and conduct research together. Objectives To propose a model for good practice in co‐researching with carers of people with dementia, by reporting and synthesizing the personal reflections of the academic and lay researchers around the methodological issues, benefits, and challenges of co‐research. Design An academic researcher and two lay researchers with lived experience of caring with someone with dementia collaborated in all stages of a qualitative research study, including development of the research protocol and topic guide, data collection, analysis and synthesis, and dissemination of findings. Throughout the study, the academic and lay researchers annotated reflections of their experience in personal diaries. Data from the diaries were synthesized and mapped out in a model for good practice in co‐research. Results Co‐research yielded benefits for all those involved and on research outputs. There were practicalities and challenges that required extra resources, in order to make the involvement of lay researchers meaningful and effective. Discussion The model for good practice illustrates overarching and stage‐specific guidelines, which can inform researchers and members of the public wishing to undertake good practice in co‐research.